x-1/2=1-(3x-12)/3

Simple and best practice solution for x-1/2=1-(3x-12)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-1/2=1-(3x-12)/3 equation:



x-1/2=1-(3x-12)/3
We move all terms to the left:
x-1/2-(1-(3x-12)/3)=0
We calculate fractions
x+(-(1-(3x-12)*2)/()+()/()=0
We calculate terms in parentheses: +(-(1-(3x-12)*2)/()+()/(), so:
-(1-(3x-12)*2)/()+()/(
We add all the numbers together, and all the variables
-(1-(3x-12)*2)/()+1
We multiply all the terms by the denominator
-(1-(3x-12)*2)+1*()
We calculate terms in parentheses: -(1-(3x-12)*2), so:
1-(3x-12)*2
determiningTheFunctionDomain -(3x-12)*2+1
We multiply parentheses
-6x+24+1
We add all the numbers together, and all the variables
-6x+25
Back to the equation:
-(-6x+25)
We add all the numbers together, and all the variables
-(-6x+25)
We get rid of parentheses
6x-25
Back to the equation:
+(6x-25)
We get rid of parentheses
x+6x-25=0
We add all the numbers together, and all the variables
7x-25=0
We move all terms containing x to the left, all other terms to the right
7x=25
x=25/7
x=3+4/7

See similar equations:

| 9y+10=7y-10 | | k+18=19.4 | | 5+6(2x-4)=30 | | 2(x-52+3x)=258 | | 400+75x=1000+25x= | | y=6=42 | | k/9=10/88 | | 9.78=c+3.14 | | H(t)=-4t^2+6t-1 | | 2y=-68+3(5y+1) | | 5^x-1=5^3x-11 | | v+5.8=19.2 | | 5-4-3x=-36 | | p/2=1.54 | | 3x+(x-14)=33 | | 8u=456 | | 8u=455 | | n+(n+1)+(n+2)+(n+3)+55=3(n+4) | | c/27=7 | | -5y(y-5)=-3y+45 | | 8-2(12+12)=5-2x-13 | | 5-4|-3x|=-36 | | r-5=43 | | -4b=-8-6b^2+4b | | c+25=671 | | 4+9.75x=0.25x+ | | 5+5(n-1)=19 | | -(x+3)+4x=6 | | n+(n+1)+(n+2)+(n+3)+(n+4)=55 | | 10+7.5n=8+7.9n | | 128=k-39 | | h+94=891 |

Equations solver categories